Evaluasi Pelatihan Level Ii (Pembelajaran) Peserta Pelatihan Fungsional Dasar Penyuluh Pertanian Ahli - Widiyanto, Adi (Chlorophyl, 2023)
This research aimed to find out the effectiveness of training at level II, based on the theory of Four Levels Kirkpatrick. The training that we observed in this study  Respondent in this study is all partisipants  of basic training of functional position of agricultural extension workers. The evaluation results show that the level of mastery of the material that has been taught obtained a score of 3.91 which is in the good category. The results of the evaluation of the attitudes  of the participants averaged 83.13 with very good criteria. By comparing pre and post-testdata using paired samples t-test,the resultsshown that there are significant difference in knowledge before and after attending the training